Robotics: Science and Systems VIII 2012
DOI: 10.15607/rss.2012.viii.023
|View full text |Cite
|
Sign up to set email alerts
|

Robust Object Grasping using Force Compliant Motion Primitives

Abstract: Abstract-We address the problem of grasping everyday objects that are small relative to an anthropomorphic hand, such as pens, screwdrivers, cellphones, and hammers from their natural poses on a support surface, e.g., a table top. In such conditions, state of the art grasp generation techniques fail to provide robust, achievable solutions due to either ignoring or trying to avoid contact with the support surface. In contrast, we show that contact with support surfaces is critical for grasping small objects. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 17 publications
(19 reference statements)
0
54
0
Order By: Relevance
“…We present three simple, yet effective, manipulation primitives for robust grasping (and releasing) of small objects from support surfaces [4]: (1) Compliant Finger Placement for bringing all fingers safely in contact with the support surface, (2) Compliant Object Grasping for maintaining the contact between the fingertips and the support surface during the finger closure, and (3) Compliant Object Release for releasing and placing the object gently on the support surface using a method similar to step 2. An example of landing and grasping primitives is shown in Fig.7.…”
Section: E Motion Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…We present three simple, yet effective, manipulation primitives for robust grasping (and releasing) of small objects from support surfaces [4]: (1) Compliant Finger Placement for bringing all fingers safely in contact with the support surface, (2) Compliant Object Grasping for maintaining the contact between the fingertips and the support surface during the finger closure, and (3) Compliant Object Release for releasing and placing the object gently on the support surface using a method similar to step 2. An example of landing and grasping primitives is shown in Fig.7.…”
Section: E Motion Planningmentioning
confidence: 99%
“…Similarly to our system, both UMan and Dexter use the combination of Barret WAM arms and hands as their manipulators which provide compliance through cable driven joints, requiring active control of compliance using accurate force sensing. Our system implements a number of active force compliant motions towards grasping and manipulation of objects [4]. HERB, developed at the Personal Robotics laboratory at Carnegie Mellon University [5], is a mobile manipulation platform developed for performing manipulation tasks in human environments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research leverages environmental constraints in the suggested manner, for example to position the hand relative to the object (Deimel and Brock, 2013), to cage objects (Kazemi et al, 2012;Deimel and Brock, 2013), or to fix an object during planar sliding (Dogar and Srinivasa, 2010;Deimel and Brock, 2013). Furthermore, specialized, simple gripper designs can exploit surface constraints such as floors to reliably pick up a large variety of objects (Xu et al, 2009).…”
Section: Interactions Between Hand Object and Environmentmentioning
confidence: 99%
“…Kazemi et al (2012) present a similar strategy; while they control hand orientation based on force feedback, we employ visual feedback.…”
Section: Surface-constrained Grasp With Barrett Handmentioning
confidence: 99%
“…In [5] the importance of first establishing and then maintaining contact (sliding) is made explicit for problems such as peg-in-hole. The DARPA ARM challenge [6] has singled out the importance of contact: several teams have published reports emphasizing that deliberate contact with the environment was key to the robust manipulation of a diverse range of objects [7], [8], [9]. Similarly, Deimel et al [10] presented an insightful study on how humans exploit tactile feedback during grasping, especially when their vision is impaired.…”
Section: Related Work a Exploiting Contacts For Manipulationmentioning
confidence: 99%